Staying Agentic in Times of Crisis: A Literature Review for a Narrative Inquiry on Female EFL Teachers - Puji Astuti; Teguh Kasprabowo; Zuhrul Anam; Girindra Putri Dewi Saraswati (Institut Agama Islam Negeri Palopo, 2023)
Female English teachers make significant contributions to their field, yet stories about them are under-researched. This paper presents the framework of an ongoing narrative inquiry aimed at understanding female teachers’ agency and its role in their professional identity construction during the Covid-19 pandemic. Based on a systematic review of relevant research, the framework displays several key themes, including the significance of active learning and digital literacies, and the scarcity of narrative inquiries into female teachers. We thus argue that in order to gain insights into post-pandemic pedagogy, there is a need for studies that depict female English teachers’ agency in enacting their pedagogical competencies and showcase their continuous efforts in constructing their professional identities, despite the challenges that they face. Against the backdrop of our review, the teacher education curriculum must include course(s) on agency and identity construction.